2003
DOI: 10.1097/00000542-200308000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Using the Time of Maximum Effect Site Concentration to Combine Pharmacokinetics and Pharmacodynamics

Abstract: T(peak) is a useful pharmacodynamic parameter and can be used to link separate pharmacokinetic and pharmacodynamic studies. This addresses a common difficulty in clinical pharmacology simulation and control problems, where there is usually a wide choice of pharmacokinetic models but only one or two published pharmacokinetic-pharmacodynamic models. The results will be immediately applicable to target-controlled anesthetic infusion systems, where linkage of separate pharmacokinetic and pharmacodynamic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 0 publications
1
85
0
2
Order By: Relevance
“…This discrepancy between studies may result from differences in study designs and in criteria for the assessment of intubating conditions. In our study, the induction sequence of anaesthesia took into account the pharmacokinetics ⁄ pharmacodynamics parameters of propofol and remifentanil, so that laryngoscopy and tracheal intubation occured at the effect-site peak concentrations of both agents [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between studies may result from differences in study designs and in criteria for the assessment of intubating conditions. In our study, the induction sequence of anaesthesia took into account the pharmacokinetics ⁄ pharmacodynamics parameters of propofol and remifentanil, so that laryngoscopy and tracheal intubation occured at the effect-site peak concentrations of both agents [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…13 This decrease was due to use of a carefully standardized anesthetic induction sequence and consideration of the unique pharmacokinetic and pharmacodynamic attributes of propofol and remifentanil such that LMA insertion occurred at the time when effect-site concentration peaked for both agents. 17,18 In fact, insertion of the LMA constitutes a less noxious stimulus compared with laryngoscopy. Billard et al observed a significant increase in systolic blood pressure ([ 40%) during laryngoscopy and tracheal intubation after induction of anesthesia with propofol 2.5 mgÁkg -1 given alone, 19 whereas Hickey et al 20 reported minor cardiovascular response to insertion of LMA after the same dose of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthesia 2012, 67, [1][2][3][4][5][6][7][8][9][10][11] Editorial data. This is because standard compartmental models are unable to account for differences due to physiology (e.g.…”
Section: Simple Model Structuresmentioning
confidence: 99%